Neurosurgical Residency in Portugal: What is the National Panorama? - Nunes Dias, Lidia; Pinto Leite, Pedro; Reizinho, Carla; Cabral, José (Acta Médica Portuguesa, 2022)
Introduction: In Portugal, the number of neurosurgery residents has been rising steadily. However, there are no robust studies assessing the level of satisfaction and quality of the current training programs. The aim of this study was to describe and quantify the level of satisfaction about Neurosurgery residency in 2019, in Portugal. Material and Methods: Quantitative observational cross-sectional study based on an original questionnaire about the level of satisfaction of neurosurgical training in Portugal in 2019, sent electronically to residents and young consultants between October and December 2019. Results: A total of 37 responses were obtained from physicians aged around 29.0 (± 4.0) years old, of which 78.4% were men and 54.1% from centers in the center/south of the country/islands. Overall, 51.4% of the answers came from first three years’ residents. As for the theoretical training, there was dissatisfaction with the morbidity and mortality meetings (59.5%), existence of sessions/anatomical lab (89.2%), participation in medical education (64.9%) and in research (64.9%). As for practical training, there was dissatisfaction only towards outpatient clinics (56.8%). There is a tendency for the first surgery to occur in the first month of residency and, in ascending order, firstly a cranial trauma surgery (5.09 ± 4.59 months), then for cerebrospinal fluid diseases (5.95 ± 4.3 months), peripheral nerves (6.0 ± 7.0 months), craniotomy (6.59 ± 3.88 months) and lumbar spine diseases (11.41 ± 1.5 months). Pediatric surgery was the last type of surgery to begin (19.36 ± 20.0 months). There seems to be a generalized satisfaction with the annual (59.5%) but not with the final examination (37.8%). Conclusion: This study has succeed at being a better description of the Portuguese neurosurgical centers and of the level of satisfaction about neurosurgical training in Portugal.